2021
DOI: 10.1186/s12913-021-06775-9
|View full text |Cite
|
Sign up to set email alerts
|

An eReferral Management & Triage System for minor Oral surgery referrals from primary care dentists: a cost-effectiveness evaluation

Abstract: Objective Oral surgery referrals from NHS dental practices are rising, increasing the pressures on available hospital resources. We assess if an electronic referral system with consultant or peer (general dental practitioner) led triage of patient referrals from general dental practices can effectively divert patients requiring minor oral surgery into specialist led primary care settings at a reduced cost whilst providing care of the same or enhanced quality. One year of no triage (all referral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The authors again found that an electronic referral management system led to allocation to appropriate care for patients. 4 There are several limitations to this study. First, our study evaluated only one social media platform, the IHC, which is specifically targeted to hernia surgery and surgeons and our results cannot be extrapolated to other sites.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…The authors again found that an electronic referral management system led to allocation to appropriate care for patients. 4 There are several limitations to this study. First, our study evaluated only one social media platform, the IHC, which is specifically targeted to hernia surgery and surgeons and our results cannot be extrapolated to other sites.…”
mentioning
confidence: 94%
“…Several groups have evaluated triage-based telehealth systems as a method of referral. One of these groups is Hardman et al 3 who prospectively evaluated a symptom-based risk stratification telehealth triage strategy for referrals made to ENT specialists in the United Kingdom for suspected head and neck cancers. The authors sought to evaluate the safety of telemedicine referral in this population.…”
mentioning
confidence: 99%
See 1 more Smart Citation